Orfeu negro = Black Orpheus [videorecording (DVD)] - Bonfá, Luiz; Jobim, Antonio Carlos (Criterion collection, 1999)
Story based on the legend of Orpheus and Eurydice set against the colorful background of the carnival in Rio de Janiero. With its magnificent color photography and lively soundtrack, this film brought the infectious bossa nova beat to the United States.